THE EFFECT OF MOBILE BANKING APPLICATION AND DIGITAL BANKING SERVICES ON INCREASING CUSTOMER ACCESS TO BANK SUMUT - Apriani Hot Dame Marito Sitompul; Egi Mileniko pelawi; Ayu Ningsih; Kristi Endah Ndilosa Ginting; Mella Yunita (Mount Hope Economic Global Journal, 2024)
Mobile banking is a practical way for customers to carry out financial transactions using mobile devices. This research aims to find out whether there is an influence on mobile banking applications and digital banking services at Bank Sumut. This research uses data by distributing questionnaires to Bank Sumut customers who use mobile banking. The sample size for this research was 100 respondents. The data analysis method uses validity and reliability tests, classical assumption tests, and hypothesis tests using the SPSS application. The results of this research show that there is a simultaneous and partial influence of mobile banking application variables and digital banking services on customers at Bank Sumut. The magnitude of the influence is 49%, and the remaining 51% is influenced by other variables outside of this research.